Análise do potencial biodegradativo da levedura Saccharomyces cerevisiae na remoção de corantes têxteis e efluente coletado de uma lavanderia industrial têxtil: um estudo da biorremediação - Ercolini, Sofia Tafuri [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Technological innovation in the textile industrial area has contributed positively to the world economy, however, this innovation generates impacts to the environment due to the large production of industrial waste that is often discarded in the water bodies without adequate treatment. These pollutants from the textile industry are characterized by high coloration and difficult degradation, thus, the waste generated by the textile industry has become a major concern in terms of pollution of water resources and the alteration of their ecosystem. Among the existing treatments, bioremediation is emerging as an object of research in several areas. It is a methodology that fits the principles of Green Chemistry, since it aims at the design of microorganisms that degrade toxic substances in innocuous forms. Saccharomyces cerevisiae yeast is an optional aerobic microorganism that has the ability to adapt metabolically under aerobic or anaerobic conditions while maintaining its high growth rate. The objective of this study was to analyze the biodegradable potential of yeast Saccharomyces cerevisiae in the removal of textile dyes by the spectrophotometric analysis of molecular absorption in the visible ultraviolet region. For the best evaluation of the biodegradable potential of the yeast Saccharomyces cerevisiae, the orange and methyl indigo carmine dyes were used in this work and then applied in industrial laundry effluent. The results indicate that the yeast is capable of biodegrading both dyes. However, it showed a higher biodegradability when exposed to the indigo dye solution, reducing its coloration by 53%. In addition, the suspension was able to biodegrade the textile effluent throughout the reaction period. The yeast was able to reduce the initial effluent concentration by up to 87%, thus, bioremediation through the use of yeast Saccharomyces cerevisiae proved to be effective for the treatment of wastewater from textile laundries

A inovação tecnológica na área industrial têxtil tem contribuído positivamente para a economia mundial, entretanto, essa inovação gera impactos ao meio ambiente devido à grande produção de resíduos industriais que muitas vezes são descartados nos corpos hídricos sem um tratamento adequado. Esses poluentes provenientes da indústria têxtil são caracterizados por apresentarem alta coloração e difícil degradação, dessa forma, os resíduos gerados pela indústria têxtil têm se tornado uma grande preocupação no que tange a poluição dos recursos hídricos e a alteração do seu ecossistema. Dentre os tratamentos existentes, a biorremediação está emergindo como objeto de pesquisa em diversas áreas. É uma metodologia que se enquadra nos princípios da Química Verde, pois visa à concepção de microrganismos que degradam substâncias tóxicas em formas inócuas. A levedura Saccharomyces cerevisiae é um microrganismo aeróbio facultativo que possui a capacidade de se adaptar metabolicamente em condições de aerobiose ou anaerobiose mantendo sua alta velocidade de crescimento. Para tanto, este estudo objetivou analisar o potencial biodegradativo da levedura Saccharomyces cerevisiae na remoção de corantes têxteis através da análise espectrofotométrica de absorção molecular na região do ultra-violeta visível. Para a melhor avaliação do potencial biodegradativo da levedura Saccharomyces cerevisiae foram utilizados neste trabalho os corantes alaranjado de metila e índigo carmim, para em seguida aplicar em efluente de lavanderia industrial. Os resultados indicam que a levedura é capaz de biodegradar ambos os corantes, entretanto apresentou maior capacidade de biodegradação quando exposta à solução do corante indigóide, reduzindo sua coloração na média de 53%. Ademais, a suspensão foi capaz de biodegradar o efluente têxtil durante todo o período de reação. A levedura conseguiu reduzir...
Keywords: Resíduos industriais; Biorremediação; Leveduras; Saccharomyces cerevisiae; Corantes; Indústria têxtil; Águas residuais - Purificação; Factory and trade waste